1995
DOI: 10.1084/jem.181.3.1005
|View full text |Cite
|
Sign up to set email alerts
|

The B cell antigen receptor of class IgD induces a stronger and more prolonged protein tyrosine phosphorylation than that of class IgM.

Abstract: SummaryMost mature B lymphocytes coexpress two classes of antigen receptor, immunoglobulin (Ig)M and IgD. The differences in the signal transduction from the two receptors are still a matter of controversy. We have analyzed B cell lines expressing IgM or IgD antigen receptors with the same antigen specificity. Cross-linking of these receptors with either antigen, or class-specific antibodies, results in the activation of protein tyrosine kinases and the phosphorylation of the same substrate proteins. The kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 61 publications
(87 reference statements)
3
33
0
Order By: Relevance
“…Potential Ags for IgM a B cells should be no different between 3H9-and 3H9R Tg BWF 1 mice; however, IgM a B cells in 3H9R but not 3H9-Tg BWF 1 mice expressed IgD and could switch V H 3H9 or a different V H generated by editing on the Tg allele to IgG or other constant regions. Recently reported results have indicated that IgD may be important for B cell activation and germinal center formation (37,38). Likewise, signaling through B cell surface IgG is more effective for signaling activation, and consequently, the induction of more clonal expansion than signaling through IgM (39).…”
Section: Anergy In Igm Aϩ B Cells In Conventional 3⌯9-and Knock-in 3hmentioning
confidence: 99%
“…Potential Ags for IgM a B cells should be no different between 3H9-and 3H9R Tg BWF 1 mice; however, IgM a B cells in 3H9R but not 3H9-Tg BWF 1 mice expressed IgD and could switch V H 3H9 or a different V H generated by editing on the Tg allele to IgG or other constant regions. Recently reported results have indicated that IgD may be important for B cell activation and germinal center formation (37,38). Likewise, signaling through B cell surface IgG is more effective for signaling activation, and consequently, the induction of more clonal expansion than signaling through IgM (39).…”
Section: Anergy In Igm Aϩ B Cells In Conventional 3⌯9-and Knock-in 3hmentioning
confidence: 99%
“…[8][9][10][11] Attachment of bulky oligosaccharides to V-region glycosylation sites may affect antigen binding. For this study, we first investigated the consequence of FL-type glycosylation for the interaction with antigen of the model BCRs B1-8, specific for hapten 4-hydroxy-3-nitrophenylacetic acid or 4-hydroxy-3-iodo-5-nitrophenylacetyl (NIP) [31][32][33] and for the HyHEL10 (Hy10) BCR specific for hen egg lysozyme (HEL). 34 We therefore introduced N-glycosylation sequons into the model BCRs based on alignments to our own and published sequences.…”
Section: V-region Mannosylation Interferes With Antigen Binding Of Momentioning
confidence: 99%
“…This would indicate that IgM and IgD are redundant receptors. In contrast, differences in tyrosine phosphorylations mediated by IgM or IgD have been observed in transfected B cell lines [30] or between mature and immature B cells [31], respectively. More data will be needed to finally resolve this enigma.…”
Section: Discussionmentioning
confidence: 99%